(untitled) (Damascus University Journal for legal sciences, 2024)
The special nature of intellectual property in terms of considering whether it is property or not and the nature of the rights that flow from it, whether they are real rights, personal rights, or a mixture of the two. All of this specificity that has emerged around intellectual property has made the question remain as to whether it is possible to consider the litigations that arise from it. It is being raised by arbitration, especially since intellectual property is, in one way or another, an important economic and commercial partner in building the global economy today, and therefore it is necessary, and in order to give it some of the flexibility that the global economic system requires, it makes it necessary to think about introducing arbitration as a partner in solving it. Litigations that arise over intellectual property, this requires the need to consider the relationship of intellectual property to the public system.